On Jordan Triple Derivations of prime Γ-Rings (International Journal of Engineering and Computer Science, 2014)
In this article, we develop some important results relating to the concepts of triple derivation and Jordan  define triple derivation and Jordan triple derivation of gamma rings. Through every  triple derivation of a gamma ring M is obviously a Jordan triple derivation of M, but the converse statement is in general not true. Here we prove that every Jordan triple derivation of a 2-torsion free prime gamma ring is a derivation